Case report: Denosumab-associated acute heart failure in patients with cardiorenal insufficiency - Xing, Yuexian; Ju, Sicong; Sun, Mengyu; Xiang, Shoukui (Frontiers in Endocrinology, 2022)
Denosumab is a pivotal treatment for postmenopausal women with osteoporosis. Although its clinical use is generally well tolerated by patients, denosumab in patients with renal insufficiency may increase the risk of hypocalcemia. Thus, we have to consider the population of denosumab in the treatment of osteoporosis and preventive measures for related complications. In a patient with cardiorenal insufficiency, we reported a case of denosumab-induced hypocalcemia complicated by acute left heart failure due to delayed administration of active vitamin D and calcium supplements. The patient's symptoms did not improve after anti-heart failure treatment. However, after adequate calcium and vitamin D supplementation subsequently, the patient's symptoms of heart failure were rapidly relieved, and the serum calcium level returned to normal within three weeks. Therefore, our case showed that the application of denosumab in patients requires assessment of cardiac and renal function, timely calcium and vitamin D supplementation, and enhanced monitoring of blood calcium levels to prevent acute left heart failure induced by denosumab-related hypocalcemia.